Pengaruh Latihan Shadow Dan Shuttle Run Terhadap Footwork Olahraga Bulutangkis Usia 13 - 15 Tahun Pb Jaya Raya Jakarta - Febri Prasetyo Ari Wibowo; Novita; Asrori Yudhaprawira; Eskar Tri Denatara; Juli Candra (Journal Coaching Education Sports, 2022)
This research aims to find out the influence of shadow and shuttle run exercises on badminton sports footwork aged 13 - 15 years at PB Jaya Raya Jakarta. It used experimental methods with two groups pre-test-post-test design.The population in the study was athletes of PB Jaya Raya Jakarta numbered 30 people.Sampling technique used purposive sampling, with criteria namely: (1) the list of attending the last two months of training was at least 75% (activeness following training), (2) the player was an athlete of PB Jaya Raya Jakarta, (3) aged 13-15 years, (4) male.Based on these criteria that meet the number of 20 athletes. Foot movement agility instruments used foot circuit test instruments.Data analysis was using the t test. Based on the results of the study, it can be concluded that: (1) There was an influence of shadow training on the footwork of badminton sports aged 13-15 years PB Jaya Raya Jakarta, with thitung 3,289 > ttabel 2,26and significance value of 0.009 < 0.05 with an influence of 9.55%.(2) There was the influence of shuttle run training on badminton footwork aged 13-15 years PB Jaya Raya Jakarta, with a thitung 4,155 > ttabel 2,26 and a significance value of 0.002 < 0.05 with an influence of 10.69%.(3) The shuttle run method is more effective for badminton sports footwork aged 13-15 years PB Jaya Raya Jakarta than shadow method with an average post-test difference of 0.2619.